2021
DOI: 10.1186/s12955-020-01660-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social support, hope and resilience on depressive symptoms within 18 months after diagnosis of prostate cancer

Abstract: Background The prevalence of depression symptoms and related modifiable factors in prostate cancer (PCa) are not well evaluated. We aimed to assess the effects of perceived social support, hope and resilience on depressive symptoms within 18 months after diagnosis of PCa, and to evaluate the role of hope and resilience as mediators of that relationship. Method A cross-sectional study was analyzed in consecutive inpatients with PCa during the months… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 45 publications
4
19
1
Order By: Relevance
“…The psychological resilience of patients with advanced lung cancer was closely related to patients' QoL (17,18). Depressive symptoms were very common in patients with prostate cancer and could affect the patient's willingness to live (19). In our study, the psychological resilience of NPC patients improved to some extent within 1 year after receiving IMRT treatment, and the average CD-RISC score increased from 55.8±7.0 to 58.4±7.8 within the 1-year period.…”
Section: Discussionmentioning
confidence: 99%
“…The psychological resilience of patients with advanced lung cancer was closely related to patients' QoL (17,18). Depressive symptoms were very common in patients with prostate cancer and could affect the patient's willingness to live (19). In our study, the psychological resilience of NPC patients improved to some extent within 1 year after receiving IMRT treatment, and the average CD-RISC score increased from 55.8±7.0 to 58.4±7.8 within the 1-year period.…”
Section: Discussionmentioning
confidence: 99%
“…These situations are negatively associated with their psychological health (27). As previous studies showed that high levels of social support were related to the improvement of psychological wellbeing among mothers of children with autism spectrum disorders (28) and reduction of depressive symptoms in patients with prostate cancer (29). In other words, a powerful support network can assist parents to cope with difficulties and maintain family members' mental wellbeing.…”
Section: Introductionmentioning
confidence: 98%
“…The depression of patients with advanced cancer is affected by multiple factors of body, mind, society and spirit. Previous studies have shown that depression is negatively correlated with hope and social support [ 9 ]. A study had built a mediating effect model to explore the mechanism of hope for depression [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the mechanism of depression can provide a reference for the intervention and treatment of patients with depression in the future. Although previous studies have explored the relationship and interaction between hope, social support, spiritual coping, and depression respectively [ 9 , 11 , 16 , 20 , 26 , 27 ], and a study has verified the mediating role of social support between hope and depression [ 18 ], but spiritual coping has not been added to the model to verify their interactions. A serial multiple mediating model was thus performed to examine the relationships among hope, social support, spiritual coping and depression.…”
Section: Introductionmentioning
confidence: 99%